Clomipramine Induced Extrapyramidal Symptoms: A Case Series - Disha Mukherjee; Madhurima Khasnobis; Anirban Ray (Journal of Clinical and Diagnostic Research, 2023)
Extra Pyramidal Symptoms (EPS) are a group of symptoms that include dystonia, bradykinesia, tremor, akathisia, and tardive dyskinesia. They are caused by the blockage of D2 receptors in the nigro-striatal pathway and the imbalanced acetyl choline activity that results in the basal ganglia. It most likely happens when first-generation antipsychotics taken in large doses and some second-generation antipsychotics. A few tricyclic antidepressants, including amitriptyline and clomipramine, monoamine oxidase (MAO) inhibitors, such as phenelzine, and SSRIs, such as fluoxetine, may also cause EPS. Antiemetics (domperidone), antiepileptic medications like phenytoin and carbamazepine, and anti-migraine medications like sumatriptan are a few additional causes of EPS. Schizophrenia patients who have never been prescribed medication may also exhibit similar movement problems. The tricyclic antidepressant (TCA) clomipramine is a tertiary amine that has potent D2 blocking and serotonin and norepinephrine reuptake inhibitor characteristics. Constipation, dry mouth, nausea, dizziness, drowsiness, tachycardia, sweating, arrhythmia, and seizures at high doses are common side effects associated with clomipramine. In this case series, three patients from different age groups are presented, the first one being a 38-year-old female with a diagnosis of paranoid schizophrenia, the second one was a 26-year-old male with the obsessive compulsive disorder (OCD)- washer type, and the third one was a 62-year-old female with dementia all of whom developed signs of EPS like dystonia, bradykinesia and tremors following the introduction of clomipramine. In all the patients, the drug was stopped and the patients were cured. This case series stresses that a clinician should be cautious about the possibility of extrapyramidal side effects while using the TCA Clomipramine which is commonly known for its anticholinergic side effects.